The effect of escape room clinical evaluation method on satisfaction, learning, and preparedness to practice as interns of nursing students: A quasi-experimental quantitative study - Najmeh Ghiamikeshtgar; Fereshteh Ghaljaei; Mahnaz Ghaljeh; Bentolhoda Taherizade; Nasrin Mahmoodi; Simin Sharifi (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Clinical evaluation utilizing the escape room game is recognized as a novel method for assessing the team-oriented performance of learners. It is a tool for evaluating teamwork skills in clinical settings, which can boost student motivation and learning. This study aimed to investigate the effect of clinical evaluation through escape rooms and feedback provision through the PEARLS (promoting excellence and reflective learning in simulation) approach on pre-internship nursing students' satisfaction, learning, and preparedness to practice as interns. MATERIALS AND METHOD: The current research is a quasi-experimental quantitative study conducted with a census sample of 42 sixth-semester undergraduate nursing students in 2022. The escape room method was utilized to evaluate entry preparedness into the clinical field. Reliable and valid researcher-made questionnaires were administered to assess the impact of the intervention on learning, satisfaction, and preparedness. The data were analyzed in SPSS version 26 using descriptive and inferential tests. The significance level was considered to be less than 0.05. RESULTS: Twenty-six males and 16 females constituted the 42 participants (mean age: 23.46 years). The clinical evaluation method of the escape room game was deemed satisfactory or highly satisfactory by 80% of students. From the perspective of 72% of students, escape rooms were definitely or highly effective in shaping their preparedness to enter the clinical field. Comparing the students' mean learning scores (self-assessment of clinical skills) before and after the test revealed that their post-test scores (55/16 ± 13/33) were significantly higher than their pre-test scores (45/58 ± 16/58) (P < 0.001). CONCLUSIONS: It appears that using the escape room evaluation method in conjunction with other student evaluation methods has helped improve students' interpersonal communication, problem-solving skills, critical thinking, and teamwork. The experience of working in a group not only improves these skills and is enjoyable to students but can also enhance their learning. Clinical education is dependent on teamwork. The escape room test can be viewed as a valuable tool for encouraging students to collaborate as a team. Therefore, it is suggested that students in all medical education groups be evaluated clinically using this test.